ADOPSI E-COMMERCE DI NEGARA BERKEMBANG - Abu Muna Almaududi Ausat; Suherlan Suherlan (JURNAL LENTERA BISNIS, 2022)
Many business organizations in developing countries are enthusiastic about implementing systems e-commerce for their business success because there has been a shift in shopping trends from offline to online. Therefore, many theories and frameworks have been developed for the implementation of e-commerce in order to increase the success of an adoption and have found different or inconsistent results. This study aims to find the problems of adoption of e-commerce in some developing countries by using descriptive qualitative research methods through a secondary data analysis approach that is expected to dig deeper into the various factors that adopt e-commerce in the developing countries. This study arrived at the conclusion that the use of technology in one country may not be implemented in another or certain countries without re-examination and reconsideration, because each country has a unique situation that requires a strategy that is in accordance with the capabilities of resources, culture, infrastructure, IT literacy and specific for the adoption of e-commerce for business organizations in it. Although in recent years, research on e-commerce in developing countries has begun to increase, researchers must continue to examine what are the drivers and barriers to the use of e-commerce in a business organization so as to enrich the literature and solutions to improve quality. the developing country's economy.Keywords: adopsi E-commerce, Developing Countries